PEMAHAMAN PERILAKU SEBAGAI DASAR PENENTUAN REWARD YANG TEPAT AGAR KINERJA INDIVIDUINDIVIDU DALAM PERUSAHAAN MENINGKAT - Nung Harjanto (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2011)
Proper rewards usually are used to stimulate employees in the organization to give their best effort in order to support the organization goal. When rewards are given, their types and amounts should be considered and related to the different level of staffs and managements in the organization which also impacts to the differences in organization individuals’ motivations. The management has to fine how to determine proper rewards so by it the employee performance hopefully also can be increased. When the employee performance increases, the organization can achieve its goal effectively and efficiently. To determine proper reward, the management has to understand employee’s behaviors because they usually reflect their satisfaction of the result of their efforts and their current condition. It also should be understood that employees’ behaviors usually also reflect employees effort to try to achieve their better life.